Lords and lordship in the British Isles in the late Middle Ages - Davies, R. R. (Oxford University Press, 2009)
It is well known that political, economic, and social power in the British Isles in the Middle Ages lay in the hands of a small group of lords. In this book, Rees Davies explores the personalities of these magnates, the nature of their lordship, and the ways in which it was expressed in a diverse and divided region in this period.